Integrasi Sains dan Agama:: Suatu Tinjauan Epistemologi - Irawan, Irawan (Lembaga Penelitian dan Pengabdian kepada Masyarakat (LP2M) IAIN Syaikh Abdurrahman Siddik Bangka Belitung, 2016)
This paper aims to explain the theory of knowledge (epistemology) in Islam and how to integrate religious studies with other sciences. It’s neseccary to deliberate in order Muslims can be avoided from ‘epistemological panic’ (Nucholish Madjid) or ‘epistemological cancer’ (Syamsuddin Arif) that can lose human’s critical power and cause intellectual failure. This paper deals with nature and sacred texts (al-Qur‘an and hadith) as the sources of science. Of the natural sources, people can research in order to expose scientific knowledge. Whereas, from the sacred texts, Muslim can understand, interpret, and analyze ayāt al-qauliyyah, ayāt t al-kauniyyah, ayāt al-insāniyyah in order to theorize ulūm al dīn, ulūm al dunyā, and dirāsat al-Islāmiyyah (Islamic studies). Of the three kinds of ayāt can be found Islamic epistemology and integrate them with other sciences. This article concludes that du’ā, ulemas, lectures, teachers, Islamic thinkers, and so on have responsibility to act “Grounding Islamic Epistemology” (Pribumisasi Epistemologi Islam) in order the Islamic world will be progressive (in science, technology, information, and communication) and develop civilization.